PENGARUH PROGRAM PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Mariska, Revy; Tamrin, Muh.; L, Syahrir (Universitas Lancang Kuning, 2024)
This research aims to look at the entrepreneurship education program for students as well as students' entrepreneurial interests in the entrepreneurship education program process at the Faculty of Economics and Business, Muhammadiyah University of Sidenreng Rappang. This research aims to see how much influence the entrepreneurship education program has on students' entrepreneurial interest.This research is quantitative research with a descriptive approach. The population in this study was 230 students at the Faculty of Economics and Business, Muhammadiyah Sidenrebg Rappang University from the 2020-2023 class using the Proportional Random Sampling technique formula as the sample method. The total number of samples was 23 students. The data collection techniques used in this research are observation, questionnaires, documentation and literature review. The data analysis technique used was validity and reliability testing, using the help of the IBM SPSS statistics 29 application.The results of this research show that from the results of the questionnaire, the recapitulation of the Entrepreneurship Education variable was 85.45%, in the